Trophic breadth niche, prey preference and developmental time of a Balaustium sp. (Acari: Erythraeidae) from Argentina - Cédola, Claudia (2018)
Trophic breadth niche, prey preference and developmental time of an unidentified Balaustium sp. (Acari:Erythraeidae) were studied under laboratory conditions. The prey offered consisted of immature and adult stages of Tetranychus urticae Koch, Bemisia tabaci (Gennadius), Frankliniella occidentalis (Pergande) and Macrosiphum euphorbiae (Thomas). The breadth of the trophic niche increased as mites developed. All active stages of Balaustium sp. consumed more than one kind of prey. Adults were the most generalist while larvae can be considered oligophagous. Larval instar significantly selected T. urticae eggs, deutonymphs substantially chose whiteflies, and thrips nymphs and adults were non-selective, eating any type of prey they could catch. Details of the development of the different stages are provided.